2012
DOI: 10.1088/0022-3727/45/7/075204
|View full text |Cite
|
Sign up to set email alerts
|

Initiation mechanism of a positive streamer in pressurized carbon dioxide up to liquid and supercritical phases with nanosecond pulsed voltages

Abstract: In this work, the initiation process of an electrical discharge in pressurized carbon dioxide up to the liquid and supercritical phases was investigated using Schlieren and photomultiplier techniques. A pulsed positive voltage with a rise time of about 40 ns and half-width of 150 ns was applied to a point-to-plane gap. The experimental results showed that the discharge started with a primary streamer consisting of a burst primary streamer and a successive primary streamer, and a back discharge followed them. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Some researchers also used Fractal Geometry and Monte Carlo method to simulate its characteristics [21][22][23][24]. Compared with research on the streamer propagation in air, only several articles investigated the streamer propagation along the insulation surface [25][26][27][28][29][30][31]. The characteristics of streamer propagation in air and along the different dielectric materials were surveyed in [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers also used Fractal Geometry and Monte Carlo method to simulate its characteristics [21][22][23][24]. Compared with research on the streamer propagation in air, only several articles investigated the streamer propagation along the insulation surface [25][26][27][28][29][30][31]. The characteristics of streamer propagation in air and along the different dielectric materials were surveyed in [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Current analysis showed that burst contained electrons of 10 8 in SC and liquid phases. This suggests that direct ionization mechanism dominates initiation of the primary streamer [7].…”
Section: Resultsmentioning
confidence: 96%
“…1) All measured values of vsi at negative points are lower than those at the positive [7]. 2) There exists a discontinuity around the sub-critical phase in the vsi characteristic when going from gas to liquid or SC phase.…”
Section: Initiation Voltagementioning
confidence: 95%
“…A positive correlation between corona inception voltage and Vr (0.5-3 kV/ns) was reported in [22]. The identical effect of the initiation voltage on Vr could be inferred in SC-CO2 because the initiation mechanism of positive streamer in SC-CO2 is suggested a direct ionization process [18]. Consequently, it is supposed that a number of initial electrons are drifted to the needle tip by rapidly enhanced field of IPPG.…”
mentioning
confidence: 75%
“…The results showed that the generation of initial electrons under negative polarity was supposed to field emission [17]; direct impact ionization mechanism was supposed by back-discharge analysis under positive and negative polarity [18], [19].…”
Section: Introductionmentioning
confidence: 95%